Integrating Local Wisdom of Lombok Community into English Textbook - Elmiana, Dewi Satria; Zamzam, Ahmad; Apgrianto, Kurniawan; Wahab, Aulia Dwi Amalina; Riyanto, Andra Ade (ETERNAL (English, Teaching, Learning, and Research Journal), 2024)
One way to promote local wisdom values ​​is to integrate them into learning in schools, particularly in Lombok where there are some valuable local wisdom which could be integrated into English textbooks. This research aims to integrate Lombok's local wisdom values ​​ into English language teaching, particularly for junior high school level to strengthen students' character and identity to face future challenges. This research employed a Research and Development approach to produce local wisdom-based textbooks with a total population and sample of 72 students who are divided into 12 groups based on the units in each textbook which are developed. Meanwhile, the practicality of the teaching materials was assessed by 2 lecturers who taught the Textbook and Material Development course, while the object of this research was the English teaching materials for junior high school level that would be developed. So far, there has never been any action to develop materials by integrating local wisdom in the form of folk tales, especially on the island of Lombok, into reading material in textbooks. This research reveals that some important characteristics obtained from Lombok's local wisdom values ​​that can be integrated into English language learning, they are religious, tolerant and egalitarian. Religious character becomes the foundation of other characters. These different characters can be integrated into the teaching and learning process. In the teaching process, teachers adjust teaching steps by instilling religiosity, tolerant and egalitarian values, while, materials are equipped with a teacher's book which provides direction to teachers, especially regarding the interpretation of local wisdom values ​​so that they comply with competency standards and basic competencies in the curriculum which is currently being implemented in Indonesia. Keywords: English textbooks, local wisdom, religion, tolerant, egalitarian.